Overcoming the divide between freedom and nature: Clarisse Coignet on the metaphysics of independent morality. - Dunham, Jeremy (British Journal for the History of Philosophy, 2020)
Clarisse Coignet (1823–1918) played an important role in a number of the most important intellectual movements in nineteenth-century France. She grew up around and documented the leaders of the Fourierist movement, provided the philosophical support for La Morale indépendante (an influential movement that promoted the rebuilding of French society on the basis of free morality, rather than religion), and spent twenty years defending the secularization of education and improving French primary schools. She developed her own theoretical and practical philosophy and applied it in the social world to play her part in the transformation of her country into a "free republic". Despite all of this, her work has received very little philosophical attention. This article focuses on the theoretical underpinnings of her practical philosophy, and the importance of her engagement with the French spiritualist tradition for its development.